Internet rzeczy w nowoczesnym leśnictwie - Mielcarek, Miłosz; Konieczny, Adam; Sobolewska, Longina; Stereńczak, Krzysztof; Talarczyk, Andrzej (Leśne Prace Badawcze, 2025)
Modern forestry faces significant challenges related to climate change and the need for sustainable management. Traditional forest monitoring methods are often insufficient for rapid responses to threats such as fires or pest outbreaks. This article presents the concept of the Internet of Things (IoT) as a technological solution to these challenges. It discusses how networks of environmental and acoustic sensors, integrated within „Smart Forest” systems, enable continuous and automated data collection. The text also introduces the idea of Digital Twins – advanced virtual models that support precise planning and decision-making by combining data from IoT and remote sensing. Furthermore, the article provides examples of IoT implementations in Poland and worldwide, outlining the key opportunities and barriers associated with implementing this technology in forestry.